Frequency of superoxide dismutase 1 c.118: G˃A mutation associated with canine degenerative myelopathy in German Shepherd dogs from Uruguay and Paraguay - Rody Artigas; Carolina Menchaca; Liz Castro; Alejandra Mondino; Yamila Perdomo; Facundo Bera; Sofía Stagno; Micaela Borca; Natalia Mendez; José Ramirez; Silvia Llambí (Veterinary World, 2024)
Background and Aim: Canine degenerative myelopathy (DM) is an autosomal recessive inherited disease that affects different dog breeds. It has an invariably fatal outcome once the clinical symptoms begin. This study aimed to investigate the population behavior of the mutation superoxide dismutase 1 (SOD1) c.118: G˃A responsible for the high risk of developing DM in two populations of German Shepherd dogs from Uruguay and Paraguay.